(untitled) (Theatrum historiae, 2011)
Cividale del Friuli (Forum Iulii) treasures a gospel-book known as Codex Foroju- liensis, which was written during the 6th century. For centuries, the Codex was considered St. Mark’s autography; therefore the manuscript itself was seen as a relic of extraordinary value. Not surprisingly, it contains about 1500 inscriptions of names, most of them written during the 9th and 10th centuries. The codex most probably served as some kind of liber vitae, since most of the inscriptions are not sentences, but just names. I believe that one of those sentences clearly indicates that the codex had been deposited in the monastery in Romagna, at least during the period of the 9th and 10th centuries. The monastery was situated not far away from Ravenna (the place where the base for preparing missions to Central Europe was later founded by Otto III). Another interesting fact is that about 300 inscriptions are names of Slavic origin. The existence of those inscriptions convinced me that the path for Christian missions to Central Europe was already opened in the 9th century, and also that it served for travels of the Slavs to Italy (often through Romagna) as well. Otto III had the milieu already prepared to continue with the contacts with Central Europe.